2015
DOI: 10.1038/srep13668
|View full text |Cite|
|
Sign up to set email alerts
|

Frankincense and myrrh suppress inflammation via regulation of the metabolic profiling and the MAPK signaling pathway

Abstract: Frankincense and myrrh are highly effective in treatment of inflammatary diseases, but lacking of the therapy mechanisms. We undertook this stuty to evaluate the effects on Adjuvant-induced Arthritis (AIA) rats and to explore the underlying mechanisms by analyzing the metabolic profiling and signaling pathway evaluated by expression of inflammatory cytokines, c-jun and c-fos and corresponding phosphorylation levels. The results stated the elevated expression levels of TNFα, PGE2, IL-2, NO, and MDA in serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Frankincense and myrrh, classical traditional Chinese medicine, are commonly used in Chinese medicine as anti-inflammatory and analgesia drugs. Vitro studies have shown that frankincense, which has been commonly believed the efficacy substance is boswellic acid, have anti-inflammatory activity [2], analgesic [3], immunosuppressive and antitumor activities [4]. The main components in myrrh are volatile oils, including monoterpenoid and sesquiterpenoids, having the same effect as frankincense [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Frankincense and myrrh, classical traditional Chinese medicine, are commonly used in Chinese medicine as anti-inflammatory and analgesia drugs. Vitro studies have shown that frankincense, which has been commonly believed the efficacy substance is boswellic acid, have anti-inflammatory activity [2], analgesic [3], immunosuppressive and antitumor activities [4]. The main components in myrrh are volatile oils, including monoterpenoid and sesquiterpenoids, having the same effect as frankincense [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…MAPK pathway is responsible for the regulation of cytokine and chemokine responses [23]. The present study showed that LPS could significantly increase the phosphorylation of MAPK and NFkB, and elevated the serum levels of TNF-a and IL-6, which were significantly decreased by Sarcandra glabra and lycopene treatment.…”
Section: Discussionmentioning
confidence: 87%
“…way. 57 It has been reported that lysoPE (18:1(9Z)/0:0) was lower in adjuvant-induced arthritic rats than in controls. In our results, lysoPE (18:1(9Z)/0:0) levels were higher in the RA group than in the HC group.…”
Section: F I G U R Ementioning
confidence: 96%